2017
DOI: 10.1002/jmri.25734
|View full text |Cite
|
Sign up to set email alerts
|

Multiple breath‐hold proton spectroscopy of human liver at 3T: Relaxation times and concentrations of glycogen, choline, and lipids

Abstract: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:410-417.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 42 publications
(104 reference statements)
0
17
0
Order By: Relevance
“…A dedicated localized 1 H MRS study on absolute metabolite levels of the liver in 44 middle‐aged subjects reports a tCho value of 8.6 ± 3.1 mmol/kg wet weight (range 3.8–17.6) . A recent similar study arrived at a mean tissue content of tCho in the adult healthy liver of 7.4mM/kg wet weight (range 4.9–10.4) . The variation in tCho content in the adult liver seemed largely due to the increase of this content with age.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…A dedicated localized 1 H MRS study on absolute metabolite levels of the liver in 44 middle‐aged subjects reports a tCho value of 8.6 ± 3.1 mmol/kg wet weight (range 3.8–17.6) . A recent similar study arrived at a mean tissue content of tCho in the adult healthy liver of 7.4mM/kg wet weight (range 4.9–10.4) . The variation in tCho content in the adult liver seemed largely due to the increase of this content with age.…”
Section: Discussionmentioning
confidence: 93%
“…It is well known that these times are increased in primary and metastatic tumors, [38][39][40] although there are only few reports of studies at 3 T. In hepatic cancers an average T 2 for the methyl protons in tCho of 133 ms was reported 14 ; this is about twice that of tCho protons in normal healthy liver. 19,29 Water proton T 2 increases about 1.5-to 2-fold in tumor lesions compared with normal liver tissue. 38 From these relaxation times we estimate that the mean tissue levels of tCho of tumorous lesions, using the water signal as a reference at a T E of 30 ms and T 2 values for normal liver, differ by less than 10% from calculations taking T 2 relaxation time for tumorous tissue into account.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans a daily variation of 20 % has been observed by ultra-sound [88]. More recently, Weis et al observed a 50 % reduction in liver glycogen within one day [89] and as glycogen also binds water, this further illustrates the variable hydration of the liver. To compare the hydration effects on PDFF and RFC, lets express PDFF and RFC as V w and V o : 18) and RFC:…”
Section: Fat-referenced Mri and Pdffmentioning
confidence: 96%